Respostas

2013-12-15T14:20:46-02:00
A)7x²-x=0                  a=7 , b=-1 ,c=0
delta = b²- 4.a.c
delta = (-1)- 4.7.0
delta = -1-0
delta = -1(raiz de delta)

x1 = -b +ou - raiz de delta /2a

x1= 1+(-1)/2.7

x1=0/14  x1=0

x2 = -b  + ou - raiz de delta /2a
                 
x2= -1-1 /2.7
  
x2= -2 /14    (simplificando por 2 fica -1/7)  raízes (0 e -1/7)
               

b)9x²=25        9x²-25=0
a=9 , b= -25 e c=0

delta=b
²-4.a.c
delta=(-25)
²-4.9.0
delta=625 -0
delta=625 
raiz de delta 25

x1=-b + ou - raiz de delta /2a
x=25 + 25 /2.9
x=50/18

x2=-b - raiz de delta /2a
x=25 -25 /2.9
x=0/18     x=0              (raízes:50/18 e 0)